Actualizing Qur’anic Ethics of Iṭ‘ām al-Ṭa‘ām in Indonesia: A Thematic Exegesis for the Free Nutritious Meals Policy - Munir, Ammar; Shohibuddin, Wafa Abdul Jabbar; Husain, Muhammad Zakir (QOF, 2025)
This study examines the Qur’anic concept of iṭ‘ām al-ṭa‘ām as a normative and operational ethic for social policy, analyzing its relevance to Indonesia’s national Makan Bergizi Gratis (MBG) program launched in 2025. Responding to persistent challenges in child nutrition and food security, exemplified by 21.5% stunting prevalence in SSGI 2023, the study addresses structural inequalities in access to nutrition highlighted by the Global Nutrition Report 2024. Employing a thematic Qur’anic exegesis (tafsīr mawḍū‘ī), the research integrates lexical–semantic analyses of feeding-related verses, Makkiyah–Madaniyah contextualization, and classical and modern exegetical insights, operationalized via maqāṣid al-sharīʿah and the Capability Approach. Findings reveal that Qur’anic discourses on iṭ‘ām al-ṭa‘ām articulate not only distributive justice and protection of vulnerable populations but also the mechanisms through which institutional design, governance, and community practices shape the realization of human capabilities. This framework allows a critical assessment of MBG’s transformative impact beyond logistical delivery, providing evidence-based guidance for ethically coherent and socially effective nutrition policies. The study contributes methodologically by advancing an Applied Social Exegesis model that bridges Qur’anic ethics with contemporary policy evaluation.